Informal Islamic education in Russia since the fall of the Soviet Union - Akhmetova, Elmira (2017)
This paper aims at reviewing informal Islamic education among Russia’s Muslims since the fall of the Communist regime in 1991. The decade of absolute religious freedom enabled various types of Islamic ideas and guides to flow into the country, as its Muslim population was thirsty for any type of knowledge about Islam after long years of anti-religious propaganda. Within few years, the country experienced the mushrooming of Islamic madrasahs and various kinds of religious literature, financed by foreign organisations and riches. The paper finds that the majority of these early Islamic educational institutions, which played the crucial role in formulating the Islamic worldview and Muslim elite in Russia, were informal without formal registration, nor having of proper curriculum or textbooks. The paper also finds that the majority of Muslims in Russia today obtain knowledge on specific issues in Islam through social networking and internet, where the government tries to control the stream of foreign ideas into the country by banning of Islamic movements, certain Islamic books and ideas. These restrictions on Islamic literature and activities had been proliferated after the tragedy of September 11, 2001, and affected the well-being and security of local Muslims. Another kind of informal Islamic education in Russia is carried out by local preachers and mullas. The paper also discusses the issues related to the recognition of certificates obtained at different foreign Islamic institutions. Lastly, the paper suggests that, at large, Russia’s Muslims obtain the basic knowledge about Islam in their families and communities, as well as through social media and other means of informal Islamic education. Only limited number of local Muslims enrol at formal Islamic educational institutions.